Analytical Study Of Sport Globalization from Iraqi Central Federation Administrative Bureaus' Point of View - Manahel Abduljabar Khazaal; Luay Husaien Albakri (College of Physical Education and Sport Sciences, 2021)
The importance of the research lies in globalization that affected all aspects of life including sports. The research aimed at building sport globalization scale as well as identifying sport globalization. The researchers used the descriptive on (373) members representing (25) Olympic federation and (22) non-Olympic federation.  The data was collected and treated to conclude a sport globalization scale that can be applied to the subjects in addition to that, there are positive and negative effects of sport globalization on the sports community. The researchers recommended the necessity of using the sport globalization scale, holding developmental courses, benefiting from the advantages of globalization, and making similar studies on other subjects.